Pancreatic tubercular abscess in a patient of disseminated tuberculosis - Patto, Shoiab Mohd; Thoker, Zubair Ahmad; Raina, Adnan Firdous (International Journal of Research in Medical Sciences, 2017)
Pancreatic tuberculosis is a rare clinical entity, despite the high prevalence of tuberculosis worldwide. When present pancreatic TB is seen usually associated with military/ disseminated TB in immuno-compromised patients with HIV topping the list in recent times. Here we present an unusual case of an immuno-competent individual with disseminated tuberculosis including pancreatic tubercular abscess a 30-year- old female was admitted with 3 months history of productive cough, constitutional symptoms and persistent epigastric discomfort. Patient had pallor and was febrile with no mass palpable per abdomen. Ultrasonography (USG)/ Contrast enhanced computed tomography (CECT) of abdomen showed cystic pancreatic lesion. Acid fast bacilli (AFB) were demonstrated in sputum as well as material obtained from USG guided fine needle aspiration (FNA) of pancreatic lesion which after 6 weeks of incubation showed growth of mycobacterium tuberculosis (MTB) confirming diagnosis of disseminated tuberculosis with pancreatic involvement. Patient was put on antitubercular therapy (ATT) and response was excellent. This case highlights that TB can affect nearly every organ of the body. It should be kept among differentials while evaluating pancreatic lesions. With adequate treatment it is curable.